SBU Accepting Float, Band Registrations for Homecoming Parade - Office of Marketing & Communications (Southwest Baptist University, 2021)
Southwest Baptist University will host the annual Homecoming parade at 10 a.m., Saturday, Oct. 2. Local businesses and organizations are invited to have a float or participate in the parade.